The role of agriculture and agro-processing for development in Jordan - Figueroa, Jose Luis; Mahmoud, Mai; Breisinger, Clemens (International Food Policy Research Institute, 2018)
This paper aims to support the implementation of the strategic development plans of Jordan by analyzing the role of agriculture and farmers in the Jordanian economy, the role that productivity and structural change can play for fostering agricultural growth, and the role agro-processing may play in Jordan’s economic development. We argue that the development of the agro-processing sector often has stronger backward and forward linkages with the agricultural sector than other sectors and, thus, plays an important role for rural transformation.